19.5 μW ultra‐low‐power 13.56 MHz RFID tag based on transparent zinc‐oxide thin‐film transistors. Issue 5 (10th July 2020) - Ma, Xiaoyu; Han, Yan; Han, Leixiao; Ye, Zhi
Abstract : A novel systematic technological process for ZnO‐thin‐film transistors (TFTs) fabrication was developed which turned out to achieve near‐zero threshold voltage devices with good performance and stability. A deuterium implantation method was realised as well to fabricate depletion n‐type ZnO TFTs. The inverters based on enhancement/depletion ZnO TFTs reached nearly full swing (0.01–5 V at 5 V V DD ) and pretty large noise margin ( V NML = 1.01 and V NMH = 3.61 V). Moreover, a transparent radio‐frequency identification (RFID) tag chip based on ZnO TFTs was developed. This tag with an anti‐collision algorithm for ISO‐14443 type‐A was first realised under 5 µm ZnO‐TFT technology. The proposed RFID tag exhibits ultra‐low‐power dissipation of <19.5 µW at 3 V V DD and a reasonable chip area of 4.7 mm 2 .